Visualizing the Future of Knowledge Sharing in SMEs in the Construction Industry: A VOSviewer Analysis of Emerging Trends and Best Practices - Salvador López; Víctor Yepes (Advances in Civil Engineering)
This review paper systematically synthesizes existing literature on knowledge sharing (KS) and knowledge transfer (KT) in the context of small and medium-sized enterprises (SMEs) in the construction industry, updating previous research and making predictions about emerging issues. The comprehensive literature review employs three different bibliometric techniques: (1) textual analysis of keywords and abstracts to identify relevant research areas, (2) cocitation analysis of references to analyze the evolution of KS and KT in SMEs, and (3) bibliographic linkage analysis of documents to summarize the background and results. The resulting conceptual map outlines the historical development of KS and KT at individual, group, and organizational levels in the construction industry. The study emphasizes the critical significance of KS and KT for SMEs in this industry. It highlights the role of innovation and open innovation in facilitating the successful implementation of KS and KT. The analysis also reveals the need for enhanced knowledge management in SMEs through better data management, implementation of digital systems for internal management, identification of inefficiencies in KT in collaborative networks, and adjustment of knowledge management approaches to suit different cultural and geographic contexts. Finally, the paper suggests future trends in KS and KT, emphasizing the importance of collaboration, continuous learning, technological capabilities, and developing a suitable organizational culture and structure for open innovation in the construction industry. This article offers an innovative approach to KS and KT in SMEs and practical recommendations for improving knowledge management and innovation capacity in construction-related businesses. Its systematic approach and focus on SMEs in the construction industry make it highly relevant for research and business practice.